2015
DOI: 10.1101/gad.271528.115
|View full text |Cite
|
Sign up to set email alerts
|

The large N-terminal region of the Brr2 RNA helicase guides productive spliceosome activation

Abstract: The Brr2 helicase provides the key remodeling activity for spliceosome catalytic activation, during which it disrupts the U4/U6 di-snRNP (small nuclear RNA protein), and its activity has to be tightly regulated. Brr2 exhibits an unusual architecture, including an ∼500-residue N-terminal region, whose functions and molecular mechanisms are presently unknown, followed by a tandem array of structurally similar helicase units (cassettes), only the first of which is catalytically active. Here, we show by crystal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
97
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 43 publications
6
97
0
Order By: Relevance
“…Within this NTR, a helical "plug" domain and a PWI-like domain are interspersed among extended, intrinsically disordered regions. 54,55 In crystal structures of yeast Brr2 in complex with a C-terminal Jab1/ MPN-like (Jab1) domain of the Prp8 protein, the NTR runs along one entire flank of the helicase cassettes and extensively contacts both NC and CC. 55,56 Following »100 disordered N-terminal residues, the plug domain wedges between the HB and the RecA2 domains of the NC.…”
Section: Brr2 Exhibits a Unique Structurementioning
confidence: 99%
See 4 more Smart Citations
“…Within this NTR, a helical "plug" domain and a PWI-like domain are interspersed among extended, intrinsically disordered regions. 54,55 In crystal structures of yeast Brr2 in complex with a C-terminal Jab1/ MPN-like (Jab1) domain of the Prp8 protein, the NTR runs along one entire flank of the helicase cassettes and extensively contacts both NC and CC. 55,56 Following »100 disordered N-terminal residues, the plug domain wedges between the HB and the RecA2 domains of the NC.…”
Section: Brr2 Exhibits a Unique Structurementioning
confidence: 99%
“…Chemical crosslinking and mass spectrometry indicated that in solution the PWI-like domain is further displaced toward and contacts the CC. 55 Immediately preceding the NC, an irregularly structured "N-terminal cassette clamp" (NC-clamp) tightly wraps around the NC and connects its RecA and WH domains.…”
Section: Brr2 Exhibits a Unique Structurementioning
confidence: 99%
See 3 more Smart Citations